The Impact of Organisational Culture and Leadership on Employee Performance: A Study at the Regional Revenue Agency (BAPENDA) of the Tidore Islands - Fizam, La Ode; Abdurrahman, Ahmad Yani; Buamonabot, Irfandi (International Journal of Business, Law, and Education, 2026)
This study aims to examine the influence of organisational culture and leadership on employee performance at the Regional Revenue Agency (BAPENDA) of the Tidore Islands, both partially and simultaneously. A quantitative research approach was employed, with data collected through questionnaires distributed to 60 respondents. The data were analysed using SPSS software, incorporating data quality testing, classical assumption tests, and multiple linear regression analysis. The results of the F-test indicate that organisational culture and leadership simultaneously exert a significant influence on employee performance, with an F-value of 208.359 and a significance level of 0.000, which is below the 0.05 threshold. Partially, the t-test results demonstrate that organisational culture has a dominant and statistically significant effect, whereas leadership does not exhibit a significant individual impact within this specific context. Overall, the findings suggest that a strong organisational culture constitutes the primary strategic determinant of public service quality and organisational productivity at BAPENDA of the Tidore Islands.